Primary care management of women with breast cancer‐related concerns—a dynamic cohort study using a network database. (15th June 2016) - Sollie, A.; Helsper, C.W.; Ader, R.J.M.; Ausems, M.G.E.M.; van der Wouden, J.C.; Numans, M.E.
Abstract : The aim of this study was to determine the incidence, management and diagnostic outcomes of breast cancer‐related concerns presented in primary care. A dynamic cohort study was performed in the anonymised routine electronic medical records (EMRs) extracted from 49 General Practices in the Netherlands (163, 471 person‐years, women aged 18–75). Main Outcome Measures were: (1) incidence rates for breast cancer‐related concerns in Primary Care, (2) proportions of these women with and without symptoms of the breast referred for further investigation, (3) proportions of referrals (not) according to the guideline and (4) proportions of women with breast cancer‐related concerns diagnosed with breast cancer during follow‐up. Breast cancer‐related concerns are presented frequently in Primary Care (incidence rate 25.9 per 1, 000 women annually). About half these women are referred for further investigation. There is room to improve General Practitioner management, mainly for women with an increased lifetime risk of developing breast cancer. Information concerning family history of cancer is often missing in the EMR. Since cancer is rarely diagnosed during follow‐up, particularly when symptoms are absent, reduction of unnecessary concerns is plausible if identification of those without an increased risk is improved.